Business Development Management Model at Samo-Samo Recycling House Based on SWOT Analysis - Rusdiansyah, Rusdiansyah; Al Rasyid, Harun; Sosrowidigdo, Suryanto (Sinkron : jurnal dan penelitian teknik informatika, 2020)
This study aims to determine the internal and external conditions faced by the Samo Samo Recycle House, as a basis for determining the appropriate alternative strategies for recycling waste business. Strategy formulation is carried out after the identification and determination of internal and external strategic factors. Internal strategic factors are then included in the IFAS (Internal Factors Analysis Summary) matrix, while external strategic factors are included in the EFAS (External Factors Analysis Summary) matrix, and the combination of the two matrices produces a Cartesisus Diagram to determine which company is in the diagram position. From the results of the calculation above, it is known that the coordinate point is located at (y = -0,12; x = 0,39). The coordinate results are presented in the SWOT matrix diagram. After knowing the meeting point of the diagonals (X), the position of the business unit is known in Quadrant II. This position shows the Samo Samo Recycling House, then in business strategies, including: Creating new designs to attract prospective buyers, Strengthening the competitiveness of commodities through improving the quality of results and business efficiency. Quality and creative human resource development